2015
DOI: 10.1007/s12633-015-9355-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Seasonal Variations, Covariations with Minerals and Forage Value on Itchgrass’ Foliar Silicification from Sudanian Benin

Abstract: Silica (SiO 2 ) in forage grasses has been found in reducing cell-wall digestibility. This study investigates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, this was not found in some field experiments and studies in natural habitats [13,14,17,18]. Furthermore, higher Si contents were found in some laboratory-grown [19] and naturally growing grasses [13,17] under drought conditions. Hence, Si uptake and accumulation may actually increase under very low water availability conditions, especially if such an increase may protect the plant from water loss or its consequences [10][11][12][13].…”
Section: Water Availabilitymentioning
confidence: 84%
See 1 more Smart Citation
“…However, this was not found in some field experiments and studies in natural habitats [13,14,17,18]. Furthermore, higher Si contents were found in some laboratory-grown [19] and naturally growing grasses [13,17] under drought conditions. Hence, Si uptake and accumulation may actually increase under very low water availability conditions, especially if such an increase may protect the plant from water loss or its consequences [10][11][12][13].…”
Section: Water Availabilitymentioning
confidence: 84%
“…Induction of increased Si uptake and accumulation following herbivory damage has been observed in several grass species, exposed to vertebrate [1,29] and invertebrate [29,30] herbivores, as well as following artificial leaf clipping [22,23,29,31]. Nonetheless, this induction was not observed in some laboratory experiments that were conducted on other grass species exposed to locusts [32] and artificial clipping [29,31,[33][34][35], possibly because exposure periods were too short to initiate a Si uptake response or to allow Si accumulation [29]. In their literature survey, Quigley and Anderson [33] show that although increased Si uptake and deposition is commonly observed in plants that are exposed to real herbivores, exceptions are not rare.…”
Section: Herbivorymentioning
confidence: 98%
“…and Pennisetum spp. ; (7) cereals contain gluten from 5% in rice to 69% in wheat; (8) properties result in 7 anti-erosive, 10 ornamental, 17 medicinal, 15 cultural and 11 aromatic with 95 oil volatile compounds; (8) Twenty-seven bio-syntheses recorded with Dhurrin genetic control, mechanism of lipid metabolism pathway and vitamin C biosynthesis remaining concerns; (9) applications are bioenergetic, cosmetic, industrial and environmental with sequestering carbon and nitrogen into soil.…”
Section: Discussionmentioning
confidence: 99%
“…• Annual species grown in rainy season wither and die. Their reproduction requires mature seed, whose formation can be hindered by intense plant exploitation [7].…”
mentioning
confidence: 99%
“…Greger et al, (2011) reported that potassium silicate use without change to root/shoot cause to increase dry weight and nitrogen concentration in all of studied plant but phosphorus rate in silicon application was increased in wheat. Kindomihou et al, (2011) expressed that SiO2 has positive correlation with P2O5 and magnesium but had negative correlation with calcium, but between SiO2 and nitrogen has not been correlation. Sandhya et al, (2011) found that silicon foliar application increased calcium and phosphorus rate of grain and straw, as 1000-grain weight has significantly increased.…”
Section: Introductionmentioning
confidence: 97%